Redistributive taxation vs. education subsidies:fostering equality and social mobility in an intergenerational model - Andrea Schneider (Verein für Socialpolitik, 2010)
Redistributive taxation and education subsidies are common policies intended to foster education attendance of poor children. However, this paper shows that in an intergenerational framework, these policies can raise social mobility only for some investment situations but not in general. I also study the impact of both policies on the aggregate skill ratio and inequality. While redistributive taxation can raise social mobility but at the same time never reduces inequality, education subsidies can, under some conditions, achieve both simultaneously. Unfortunately, these conditions necessarily require a population in which the skill ratio is already quite high.
Keywords: I21; H24; J62; 330; Redistributive taxation; Education subsidies; Intergenerational mobility; Inequality